Comparative studies of serum and synovial fluid C reactive protein concentrations. Issue 10 (October 1987) - Rowe, I F; Sheldon, J; Riches, P G; Keat, A C
Abstract : The relation between serum and synovial fluid (SF) C reactive protein (CRP) concentrations was investigated in a variety of arthritides, including rheumatoid arthritis (RA), psoriatic arthritis, reactive arthritis, and osteoarthritis. SF CRP levels were significantly reduced compared with serum levels in the inflammatory arthritides, but there was good correlation between serum and SF values. SF CRP values were all at the lower limit of the detectable range in osteoarthritis. In patients with RA or psoriatic arthritis followed up serially through an exacerbation of arthritis, changes in SF CRP reflected closely changes in serum CRP. In patients with RA SF/serum ratios of proteins of different molecular weight were used to derive a regression equation between SF/serum ratio and molecular mass. SF/serum values for CRP were significantly less than predicted from its molecular weight, suggesting that CRP is either being selectively bound in synovium or specifically consumed in SF and may be playing an important part in the inflammatory process in RA.